Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Coral spawning patterns on the Luhuitou fringing reef in Hainan Island of the northern South China Sea - Youfang Sun; Yuyang Zhang; Lei Jiang; Xiaolei Yu; Lintao Huang; Tao Yuan; Jianhui Yang; Jiansheng Lian; Chengyue Liu; Put Ang; Hui Huang (Frontiers in Marine Science, 2024)
Observation of coral spawning times is valuable to detect spawning patterns and identify the potential mechanisms behind coral reproduction. Although large amount of data on global coral spawning records have become available over the past decades, information on coral spawning in the northern South China Sea remains scarce. In this study, we investigated the spawning patterns of scleractinian corals in Luhuitou fringing reef, Hainan Island, China, from 2009 to 2021 in relation to lunar cycles (month and day). The spawning times of 22 coral species from five genera ( Acropora , Montipora , Platygyra , Dipsastraea , and Galaxea ) within three families (Acroporidae, Merulinidae, and Euphylliidae) were recorded, with spawning occurring from lunar February to May 2009–2021. Recorded spawning events started at a period of increasing seawater temperature. Acropora , the most documented genus, spawned between lunar February and April, but primarily in lunar March. Importantly, the spawning time of Acropora was delayed for one lunar month in 2016 most likely due to a rapid decrease in monthly mean seawater temperature in lunar February. Spawning lunar days before, on or after full moon of corals in the Luhuitou Reef, including those of the Acropora species, were highly variable between years even for the same species. No predictable pattern of spawning times can thus be detected. Nonetheless, our results fill up an information gap on coral spawning patterns in the northern South China Sea that may be useful for further understanding of the reproductive biology of scleractinian corals throughout the Indo–West Pacific.

Mannitol as a resource for the growth and reproduction of Sargassum siliquastrum (Mertens ex Turner) C. Agardh - Suet Ying Wong; Put Ang (Journal of Applied Phycology, 2024)

Corrigendum to “Hong Kong's subtropical scleractinian coral communities: Baseline, environmental drivers and management implications” [Mar. Pollut. Bull. 167 (2021): 112289] - Yip Hung Yeung; James Y. Xie; Chun Kit Kwok; Keith Kei; Put Ang; Leo Lai Chan; Walter Dellisanti; Chi Chiu Cheang; Wing-kuen Chow; Jian-Wen Qiu (Marine Pollution Bulletin, 2023)

Effects of heat and hyposalinity on the gene expression in Acropora pruinosa larvae - Apple Pui Yi Chui; Yue Him Wong; Jin Sun; Taison Ka Tai Chang; Jian-Wen Qiu; Pei-Yuan Qian; Put Ang (Frontiers in Marine Science, 2023)
Introduction Climate change has resulted in elevated sea surface temperature as well as increased frequency of extreme weather events, e.g. cyclones and rainstorms, which could lead to reduced seawater salinity. While temperature effects on corals have been widely examined, the combined effects of both temperature and salinity on corals, especially their early stages, remain poorly known. This study aimed to examine how the larvae of Acropora pruinosa in a marginal coral habitat, Hong Kong, respond to high temperature (+5°C ambient, HT), low salinity (26 psu, LS), and the combined effects of both stressors (HTLS). Methods We recorded larval survival and settlement success under different experimental treatments, and used RNA-Seq technique to compare the gene expression patterns of these larvae to understand the underlying molecular mechanism of stress responses. Results Our results showed that the survivorship of coral larvae was not affected in all experimental treatments, with all larvae surviving through the 72-hour period of the experiment. Yet, larval settlement was compromised under all stress treatments. The settlement rates were 39.3%, 12%, and 0% for the elevated temperature, reduced salinity, and the combined treatment, respectively, which were all significantly lower than that under the control treatment (78%). We demonstrated that low salinity (LS) triggered responsive gene sets with functions in ATP production, protein translation, and receptor for neuroactive ligands. In addition, high temperature (HT) treatment also triggered MAPK and NF-kB signaling and apoptosis in these coral larvae. The combined stressor treatment (HTLS) acted synergistically, resulting in the up-regulation of intracellular transducers that could trigger the intrinsic apoptosis pathway. This may explain the total failure in larval settlement under HTLS that could further increase larval vulnerability in the natural environment. Discussion Our results provide new insights into the molecular responses of coral larvae and represent an essential first step in expanding ourunderstanding of the mechanisms of tolerance that may be exhibited by coral larvae exposed to multiple stressors.

Seasonal drivers of productivity and calcification in the coral Platygyra carnosa in a subtropical reef - Walter Dellisanti; Jeffery T. H. Chung; Sam K. F. Yiu; Ryan Ho Leung Tsang; Put Ang; Yip Hung Yeung; Jian-Wen Qiu; Shelby E. McIlroy; Mark L. Wells; Jiajun Wu; Leo Lei Chan (Frontiers in Marine Science, 2023)
Scleractinian corals are increasingly subjected to local stressors combined with global changes. In subtropical areas, corals exhibit metabolic plasticity and resilience in response to variability and extremes in local temperature, salinity, and light; however, the physiological mechanisms by which corals acclimate or adapt to these changing conditions remain disputed. We assessed the physiological status of the coral Platygyra carnosa during a two-year in situ monitoring survey. To obtain metabolic rates (respiration and photosynthesis), photochemical efficiency (Fv / Fm), and biocalcification measurements, non-invasive techniques such as underwater respirometry, Pulse Amplitude Modulated (PAM) fluorometry, total alkalinity measurements, and digital photography were used. Our findings show clear seasonality in water quality parameters, which affected coral health. Elevated temperatures during the summer were below the maximum monthly mean < 31°C) but reduced the energetic productivity of corals (-44% relative to winter). Fluctuations in salinity (25–38 ppt) and pH (7.65–8.44) were linked to rainfall and reduced calcification rates. The conditions during the spring were favorable for coral metabolism and calcification (+20% relative to summer). Overall, our research demonstrates that the metabolic plasticity of P. carnosa in response to shifts in seawater quality allows this species to survive ongoing environmental change. Our in situ observations provide fundamental insights into coral response mechanisms under changing environmental conditions and contribute to projections of coral health under future scenarios of global change.

Species richness and generalists–specialists mosaicism of symbiodiniacean symbionts in corals from Hong Kong revealed by high-throughput ITS sequencing - Osama S. Saad; Xin Lin; Tsz Yan Ng; Ling Li; Put Ang; Senjie Lin (Coral Reefs, 2022)

Latitudinal variation in growth and survival of juvenile corals in the West and South Pacific - Yoko Nozawa; Ronald D. Villanueva; Munasik Munasik; Kakaskasen Andreas Roeroe; Takuma Mezaki; Takashi Kawai; James Guest; Seiji Arakaki; Go Suzuki; Jean J. B. Tanangonan; Put O. Ang; Peter J. Edmunds (Coral Reefs, 2021)

A Diver-Portable Respirometry System for in-situ Short-Term Measurements of Coral Metabolic Health and Rates of Calcification - Walter Dellisanti; Ryan H. L. Tsang; Put Ang; Jiajun Wu; Mark L. Wells; Leo L. Chan (Frontiers in Marine Science, 2020)

Onset of symbiosis in planula larvae of scleractinian corals - Tsz Yan Ng; Apple Pui Yi Chui; Put Ang (Hydrobiologia, 2019)

Critical Information Gaps Impeding Understanding of the Role of Larval Connectivity Among Coral Reef Islands in an Era of Global Change - Peter J. Edmunds; Shelby E. McIlroy; Mehdi Adjeroud; Put Ang; Jessica L. Bergman; Robert C. Carpenter; Mary A. Coffroth; Atsushi G. Fujimura; James L. Hench; Sally J. Holbrook; James J. Leichter; Soyoka Muko; et al. (Frontiers in Marine Science, 2018)

Long-term study on seasonal changes in floristic composition and structure of marine macroalgal communities along the coast of Northern Taiwan, southern East China Sea - Showe-Mei Lin; Li-Chun Tseng; Put O. Ang; John Bolton; Li-Chia Liu (Marine Biology, 2018)

First observation of the nudibranch Tenellia feeding on the scleractinian coral Pavona decussata - Kwan Ting Wong; Tsz Yan Ng; Ryan Ho Leung Tsang; Put Ang (Coral Reefs, 2017)

Erratum to: Carbon dioxide mitigation potential of seaweed aquaculture beds (SABs) - Calvyn F. A. Sondak; Put O. Ang; John Beardall; Alecia Bellgrove; Sung Min Boo; Grevo S. Gerung; Christopher D. Hepburn; Dang Diem Hong; Zhengyu Hu; Hiroshi Kawai; Danilo Largo; Jin Ae Lee; et al. (Journal of Applied Phycology, 2017)

Carbon dioxide mitigation potential of seaweed aquaculture beds (SABs) - Calvyn F. A. Sondak; Put O. Ang; John Beardall; Alecia Bellgrove; Sung Min Boo; Grevo S. Gerung; Christopher D. Hepburn; Dang Diem Hong; Zhengyu Hu; Hiroshi Kawai; Danilo Largo; Jin Ae Lee; et al. (Journal of Applied Phycology, 2017)

Low symbiont diversity as a potential adaptive strategy in a marginal non-reefal environment: a case study of corals in Hong Kong - Tsz Yan Ng; Put Ang (Coral Reefs, 2016)

Did borers make corals more susceptible to a catastrophic disease outbreak in Hong Kong? - Kwan Ting Wong; Ryan Ho Leung Tsang; Put Ang (Marine Biodiversity, 2016)

Conservation of reef corals in the South China Sea based on species and evolutionary diversity - Danwei Huang; Bert W. Hoeksema; Yang Amri Affendi; Put O. Ang; Chaolun A. Chen; Hui Huang; David J. W. Lane; Wilfredo Y. Licuanan; Ouk Vibol; Si Tuan Vo; Thamasak Yeemin; Loke Ming Chou (Biodiversity and Conservation, 2016)

Extensive mortality of black corals Antipathes curvata along a depth gradient in Hong Kong, China - Apple Pui Yi Chui; Put O Ang (Marine Biodiversity, 2015)

Elevated temperature enhances normal early embryonic development in the coral Platygyra acuta under low salinity conditions - Apple Pui Yi Chui; Put Ang (Coral Reefs, 2015)

Extraordinary diversity of reef corals in the South China Sea - Danwei Huang; Wilfredo Y. Licuanan; Bert W. Hoeksema; Chaolun Allen Chen; Put O. Ang; Hui Huang; David J. W. Lane; Si Tuan Vo; Zarinah Waheed; Yang Amri Affendi; Thamasak Yeemin; Loke Ming Chou (Marine Biodiversity, 2015)

Cold temperature stress and predation effects on corals: their possible roles in structuring a nonreefal coral community - Ryan Ho Leung Tsang; Put Ang (Coral Reefs, 2015)

Assessing the potential for recovery of a Sargassum siliquastrum community in Hong Kong - Yu Hin Leung; Chung Wing Yeung; Put O. Ang (Journal of Applied Phycology, 2014)

Anti-herpesviral property and mode of action of a polysaccharide from brown seaweed (Hydroclathrus clathratus) - Hui Wang; Vincent E. C. Ooi; Put O. Ang (World Journal of Microbiology and Biotechnology, 2010)

Phylogeography of the marine macroalga Sargassum hemiphyllum (Phaeophyceae, Heterokontophyta) in northwestern Pacific - CHI CHIU CHEANG; KA HOU CHU; PUT O. ANG (Molecular Ecology, 2010)

Antiviral activities of extracts from Hong Kong seaweeds - Hui Wang; Engchoon Vincent Ooi; Put O. Ang (Journal of Zhejiang University-SCIENCE B, 2008)

Early development of germlings of Sargassum thunbergii (Fucales, Phaeophyta) under laboratory conditions - Ziguo Zhao; Fengjuan Zhao; Jianting Yao; Jingmei Lu; Put. O. Ang; Delin Duan (Journal of Applied Phycology, 2008)

Genetic structure analysis of natural Sargassum muticum (Fucales, Phaeophyta) populations using RAPD and ISSR markers - Fengjuan Zhao; Fuli Liu; Jidong Liu; Put O. Ang; Delin Duan (Journal of Applied Phycology, 2008)

Phenology of Sargassum spp. in Tung Ping Chau Marine Park, Hong Kong SAR, China - Put O. Ang (Journal of Applied Phycology, 2006)

Nutritional evaluation of protein concentrates isolated from two red seaweeds: Hypnea charoides and Hypnea japonica in growing rats - K.H. Wong; Peter C.K. Cheung; Put O. Ang (Hydrobiologia, 2004)

Hepatoprotective effect of seaweeds' methanol extract against carbon tetrachloride-induced poisoning in rats - Chun-Kwan Wong; Vincent E.C. Ooi; Put O. Ang (Hydrobiologia, 2004)

Seasonal occurrence and reproduction of Hypnea charoides (Rhodophyta) in Tung Ping Chau, N.T., Hong Kong SAR, China - Corsica S.L. Kong; Put O. Ang (Hydrobiologia, 2004)